Irrigational Projects Of Tsarist Russia In The Fergana Valley (Late 19th – Early 20th Centuries): A ScientificArcheographical Review (Texas Journal of Philology, Culture and History, 2026)
In the late 19th and early 20th centuries, the Fergana Valley underwent a profound geopolitical and economic transformation under the colonial administration of Tsarist Russia, becoming a crucial raw material base for the empire's textile industry. This study explores how the integration of the region into global capitalist networks reshaped traditional agrarian frameworks.